HUBUNGAN PENDAPATAN ORANG TUA DENGAN KETERLAMBATAN STUDI MAHASISWA (Studi Kasus Mahasiswa Bermasalah Fakultas Ekonomi Universitas Trisakti) - Farah Margaretha; husna Leila Yusran (Universitas Trisakti, 2002)
The objective of this research is to explore and to analyze the factors that influence student lateness in finishing their study at the Trisakti University. Desctiptive analyze and sector analyze are used.It conclude that there are sixfactor that causing the lateness of study period for student, there are talent, willing, physical condition, family economic situation, parents education and study facility at home and at the campus.